The Ethical Principle of Non-Arbitrariness: The Formal Moral Theory of Francisco Miró Quesada - Villarán, Alonso (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The goal of this article is to introduce, interpret, and defend the originality of the «first half» of the rational foundation of ethics of Francisco Miró Quesada Cantuarias (Lima 1918-2019). To do so, we will focus on his three first ethical works —«El Intelectual, el Occidente y la Política» (1965), «Sobre el Derecho Justo» (1976) y «Ser Humano Naturaleza, Historia» (1987)—, leaving his later works aside for a complementary work. We will show how Miró Quesada tries to refine Immanuel Kant’s moral philosophy, overcoming its possible main flaw —here called disguised materialism— and rethinking the supreme moral principle, which he calls non-arbitrariness. We will also evaluate both his thesis that the principle of non-arbitrariness is the necessary condition of ethics and his invitation to renounce looking for its sufficient condition. On the way, we will highlight the originality of Miró Quesada’s proposal. Finally, we will advance the central thesis of his later ethical works and posit brief questions that his moral theory needs to answer.